206 New educational intervention with a shorter duration of training paramedical professionals for undertaking cervical screening programme. (18th September 2019) - Shylasree, T; Mishra, G; Noronha, S; Patil, A; Nandy, P; Kattepur, A; Pramesh, C
Abstract : Objectives: To assess the effectiveness of a new training programme with a shorter duration of training for cervical cancer prevention among professional Medical Practitioners (PMPs). Methods: The new training method consisted of video based tutorials, lectures and hands on training for 2 weeks. PMPs were given personal electronic tablets consisting of video tutorials for revision during the training period. Fifty PMPs were given a questionnaire consisting of 50 questions at the start and completion of the new training programme. There were 3 category of questions: multiselect, true/false and knowledge score. The questions were further divided into 5 domains. Domain 1–5 consisted of questions on awareness of cervical cancer, cervical precancer, practical screening methodology, data management and HPV respectively. Responses were Scored by calculating the raw score and using linear transformation to standardize the raw score for all questions. Results: More than 90% PMPs were married, parous and were from primary health care centers with median work experience of 19.5 years, however only 60% had themselves undergone cervical screening. Analysis showed very significant improvement in all domains after introduction of the new training programme (p <0.0001). Conclusions: The new training programme is effective in significantly improving the skills of PMPS despite shorter training duration. The questionnaire survey was found to be effective as it tested knowledge and awareness by multiple methods to improve response accuracy.